Fixed Mindset vs. Growth Mindset: A Phenomenon in Higher Education to Achieve a Bachelor's Degree - Gita Aulia Nurani (Ilmu Inovasi Nusantara, 2022)
This study investigates students' experiences with the research process as one of Indonesia's bachelor's degree graduation requirements. The underpinning for the research procedure was Carol Dweck's notion of fixed and growth mindsets. This study followed the qualitative phenomenology method and included semi-structured interviews. Eleven undergraduate seniors or fourth-year students participated in interviews lasting 45 to 60 minutes. According to the data, students had difficulty with the three stages of the research process. (1) Erroneously identified the problem and had difficulty discussing it with the supervisor. (2) Lack of comprehension and application of the research method. (3) Insufficient scholarly writing. Moreover, individuals described two contributing elements, first, psychological factors such as motivation and the desire to conduct the independent study. Second, social issues inside the supervisory and academic institutions. Participants proposed that the complete technique course and academic writing should be taught by faculty beginning in the third year after mastery of the theoretical framework. Research involving quantitative surveys is required to determine the correlation between each internal and external variable